A Multidimensional Comparison Assessing the Viability of Electric Vehicles in Jordan Across Key Performance Metrics - Mohammad Ahmad Ben Tarief; Salah Aldeen Qasim; Hisham Al-mujafet; Saif addeen Rababa; Suleiman Abu-Ein; Sakher Alaqbawe (Automotive Experiences, 2025)
This study presents the first field-based, OBD-II”“supported comparison of an electric vehicle (Changan Eado EV300) and a gasoline vehicle (Kia K3, 2019) under realistic Jordanian driving conditions. Using a 100 km mixed-route test and annualized projections, we evaluate energy consumption, operating cost, greenhouse-gas emissions (including battery manufacturing amortization), dynamic performance, cabin noise/comfort, and payback of purchase-price premium. Results indicate that, under predominant home charging, EV energy costs are reduced by over 60% relative to the tested gasoline vehicle, and operational COâ‚‚ emissions fall substantially when charged from a low-carbon grid; battery manufacturing increases lifecycle emissions but does not offset operational benefits under renewable charging scenarios. EVs deliver superior low-speed torque and smoother acceleration, while ICE vehicles retain advantages in raw range and refueling time. Payback of the purchase premium is estimated at ~5.6”“7.5 years (without battery replacement) and can extend beyond a decade if mid-life battery replacement is required. Findings inform policy on charging infrastructure, tariff design, and battery-lifecycle management for Jordan and similar contexts.